Conduction System Pacing Versus Biventricular Cardiac Resynchronization Pacing: Meta-Analysis on Outcomes in Patients with Non-Left Bundle Branch Block - Xuanming Pung; Joe J. L. Chua; Khi Yung Fong; Yi Yi Chua; Germaine J. M. Loo; Jonathan W. S. Ong; Julian C. K. Tay; Hooi Khee Teo; Yue Wang; Colin Yeo; Eric T. S. Lim; Kah Leng Ho; et al. (Medicina)
Background and Objectives: The role of biventricular pacing (BVP) is less well-established in patients with heart failure with reduced ejection fraction (HFrEF) without left bundle branch block (LBBB). Conduction system pacing (CSP) has gained significant traction and may provide a safe and more physiological alternative to BVP in these patients. A few small studies studying this question have reported conflicting results. This meta-analysis aims to compare procedural and clinical outcomes between CSP and BVP in this group. Materials and Methods: An online literature search was systematically conducted to retrieve studies comparing CSP and BVP in HFrEF patients with non-LBBB. Four studies with 461 patients were included. Results: Implant-derived paced QRS duration was significantly shorter (mean difference [MD] −19.7 ms, 95% confidence interval [CI] −36.2 to −3.3, p = 0.0355) with CSP. Echocardiographic response with significantly greater improvement in left ventricular ejection fraction (MD 5.6%, 95% CI 3.1 to 8.0, p = 0.0106) was also observed with CSP. There were no statistically significant differences in clinical outcomes such as all-cause mortality (relative risk [RR] 0.53, 95% CI 0.18 to 1.60, p = 0.133) and heart failure hospitalization (RR 0.54, 95% CI 0.19 to 1.56, p = 0.129). Conclusions: This meta-analysis suggests that CSP may have better electrical synchrony and echocardiographic response compared to BVP in HFrEF patients with non-LBBB. Further randomized studies with longer follow-up may be required to elucidate potential benefits in clinical outcomes.